Classic phenotype of Coffin–lowry syndrome in a female with stimulus‐induced drop episodes and a genotype with preserved N‐terminal kinase domain. Issue 2 (5th December 2013) - Rojnueangnit, Kitiwan; Jones, Julie R.; Basehore, Monica J.; Robin, Nathaniel H.
Abstract An adolescent female presented with intellectual disability, stimulus‐induced drop episodes (SIDEs), facial characteristics that include wide set eyes, short nose with wide columella, full and everted lips with wide mouth and progressive skeletal changes: scoliosis, spondylolisthesis and pectus excavatum. These findings were suggestive of Coffin–Lowry syndrome (CLS), and this was confirmed by the identification of a novel mutation in RPS6KA3, a heterozygous one basepair duplication at nucleotide 1570 (c.1570dupA). This mutation occurs within the C‐terminal kinase domain of the protein, and, therefore contradicts the previous report that SIDEs is only associated with premature truncation of the protein in the N‐terminal kinase domain or upstream of this domain. As CLS is X‐linked, it is unusual for a female to have such a classic phenotype. © 2013 Wiley Periodicals, Inc.